2015
DOI: 10.1186/s13054-015-0943-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental acute lung injury induces multi-organ epigenetic modifications in key angiogenic genes implicated in sepsis-associated endothelial dysfunction

Abstract: IntroductionThe Tie2/angiopoietin (Tie2/Ang) and vascular endothelial growth factor receptor-ligand systems (VEGFR/VEGF) are recognized to play important roles in the regulation of microvascular endothelial function. Downregulation of these genes during sepsis has been implicated in the pathogenesis of sepsis-related microvascular leak and multiple organ dysfunction syndrome. Mechanisms responsible for dysregulation of angiogenic genes in sepsis are poorly defined.MethodsWestern blot, reverse transcription-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 54 publications
4
50
0
3
Order By: Relevance
“…Even when the lung is the organ of interest when regarding increased pulmonary vascular resistance, remote mechanisms may play a significant role. Recently, it has been demonstrated that epigenetic modifications (more precisely decreases in transcription‐permissive histone modifications) in various organs contribute to a downregulation of ANG1 and TIE2 in ALI and sepsis . Moreover, cell types other than EC and SMC such as specialized immune cells should be considered too .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the lung is the organ of interest when regarding increased pulmonary vascular resistance, remote mechanisms may play a significant role. Recently, it has been demonstrated that epigenetic modifications (more precisely decreases in transcription‐permissive histone modifications) in various organs contribute to a downregulation of ANG1 and TIE2 in ALI and sepsis . Moreover, cell types other than EC and SMC such as specialized immune cells should be considered too .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that epigenetic modifications (more precisely decreases in transcription-permissive histone modifications) in various organs contribute to a downregulation of ANG1 and TIE2 in ALI and sepsis. 40 Moreover, cell types other than EC and SMC such as specialized immune cells should be considered too. 41,42 Future studies should focus on these alternative sources of highly altered angiopoietin balance.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular biology of the Angpt/Tie2 signaling axis has been revealed in studies spanning more than a decade (25)(26)(27)(28). Angpt-1 is found in platelets, pericytes and especially in endothelial cells, where it acts constitutively to maintain endothelial barrier integrity.…”
Section: Angpt/tie2 Signalingmentioning
confidence: 99%
“…All rights reserved. Ann Transl Med 2016;4(21):421 atm.amegroups.com involved in the loss of endothelial barrier integrity and the ensuing plasma leakage (26)(27)(28)(29)31).…”
mentioning
confidence: 99%
See 1 more Smart Citation